2012
DOI: 10.1364/boe.4.000032
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive vasculature detection using laser speckle imaging in avian embryos through intact egg in early incubation stage

Abstract: Monitoring the vital signs of a developing embryo is very useful in avian breeding programs, especially during early days of incubation, so that dead or unfertilized eggs can be timely removed from incubator and new eggs can be placed in. A noninvasive system for detecting the vital signs of avian embryo through intact egg in early stage of incubation has been developed using laser speckle imaging (LSI). The system was based on the measurement of intensity fluctuations of speckle caused by the embryo’s blood f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 14 publications
1
18
0
1
Order By: Relevance
“…By demonstrating that the relationship between the speckle contrast (K) for the LSI and BFI from DCS, it is known that . Therefore, the BFI of DSCA system has been defined as follows: [24] However, the illumination power is adjusted as 16.11 mW to prevent any detrimental effect caused by the laser illumination power [7,25]. A detector of 16-bit charge couple device (CCD) camera (F-033B, Stringray) is used and coupled with four single-mode fibers, four detection channels.…”
Section: Measurement Of Vital Sign In Chick Embryo Using Multi-channementioning
confidence: 99%
See 1 more Smart Citation
“…By demonstrating that the relationship between the speckle contrast (K) for the LSI and BFI from DCS, it is known that . Therefore, the BFI of DSCA system has been defined as follows: [24] However, the illumination power is adjusted as 16.11 mW to prevent any detrimental effect caused by the laser illumination power [7,25]. A detector of 16-bit charge couple device (CCD) camera (F-033B, Stringray) is used and coupled with four single-mode fibers, four detection channels.…”
Section: Measurement Of Vital Sign In Chick Embryo Using Multi-channementioning
confidence: 99%
“…However, micro-MRI has limitations such as relatively slow imaging speed, expensive system, and the difficulty to use in poultry industry. Yang et al have demonstrated the changes of blood flow maps which is vasculature of chick embryo using laser speckle imaging (LSI) under illumination of a laser in early incubation stage [7]. The LSI is based on speckle intensity fluctuation depending on the blood flow of avian embryonic vasculature.…”
Section: Introductionmentioning
confidence: 99%
“…Limited imaging depth of confocal microscopy and OCT makes it difficult to view the embryo at later stages of development. Other imaging techniques like bioluminescence imaging (BLI) , intravital imaging , laser speckle imaging (LSI) , and high‐frequency ultrasound imaging are not widely used for vasculature imaging of chicken embryo as they either need external contrast agent to distinguish the embryonic tissues and organs, have poor imaging resolution or need complicated image processing algorithms to enhance the image quality. Providing the advantages of high ultrasound resolution and good intrinsic optical contrast, photoacoustic imaging (PAI) seems like a promising choice for chicken embryo imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we collect embryonic heartbeat signals to classify dead embryos and live embryos. At present, common low-risk and easy-to-perform methods used to noninvasively measure the heart rate of chicken embryos are laser speckle imaging and infrared light measuring [14]. We chose the second method, infrared light measuring, to avoid image processing.…”
Section: Introductionmentioning
confidence: 99%